ANALISIS SOAL UJIAN SEMESTER FISIKA KELAS VIII SMP FATIH BILLINGUAL SCHOOL BANDA ACEH TAHUN AJARAN 2015-2016 - Yudia Mutiara (Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2016)
This study aims to determine the level of difficulty, distinguishing power and function distractor items of physics semester exams in  class VIII SMP FatihBillingual School Banda Aceh on academic year 2015-2016. This research is a descriptive study and the approach used is qualitative. Population and sample of this research is a class VIII student FatihBillingual School Banda Aceh of academic year 2015/2016 amounted to 20 people. the result of this research is "the item of Physics semester exam at Junior FatihBillingual School Banda Aceh on academic year 2015-2016 has an easy difficulty level, bad distinguishing  power  and functioning distractors acceptable". Keywords: Analysis of Grain Problem, level of difficulty, distinguishing features, functions distractors. Penelitian ini bertujuan untuk mengetahui tingkat kesukaran, daya beda dan fungsi distraktor butir soal ujian semester mata pelajaran fisika kelas VIII SMP Fatih Billingual School Banda Aceh tahun ajaran 2015-2016. Jenis penelitian ini adalah penelitian deskriptifdanPendekatan yang digunakan adalah kualitatif.Populasi dan sampelpenelitian ini adalah siswa kelas VIII Fatih Billingual School Banda Aceh tahun ajaran 2015/2016 berjumlah 20 orang. HasilPenelitianiniadalah“soal US Fisika SMP Fatih Billingual School Banda Aceh Tahun ajaran 2015-2016 memiliki tingkat kesukaran yang mudah, daya beda yang jelek dan fungsi distraktor yang dapat diterima”.Kata Kunci :AnalisisButirSoal, Tingkat Kesukaran, Daya Beda, fungsi Distraktor